(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the problem of the definition of an investment dispute and the main categories that allow to recognize the dispute «investment». A clear definition of the basic concepts in science traditionally avoids legal incidents and disputes, but it does not apply to the definition of «investment dispute». In legal literature, the absence of a uniform definition of its causes numerous discussions. The result is that the states – participants of various international agreements on different interpretations of the term. Key words: investor, investing, investment dispute, the state.